Fu Lo-Shu: A Documentary Chronicle of Sino-Western Relations (1644-1820). Published for the Association for Asian Studies by the University of Arizona Press, Tucson, 1966, xi-771 pp. 2 vols. - Martínez Legorreta, Omar (Estudios de Asia y África, 1969)
-